A design process for a wearable hand-assistive soft robotic device allowing flexion and extension for different hand sizes - Chung, Sung bok (Stellenbosch : Stellenbosch University, 2025)
Chung, S. 2025. A design process for a wearable hand-assistive soft robotic device allowing flexion and extension for different hand sizes. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/39b9f4e0-289e-4fe5-b6a8-c77206987e0d